Finding a voice Community radio: role, sustainability and practice: Centre for the Study of Media and Culture in Small Nations, Faculty of Creative and Cultural Industries, University of Glamorgan, ATRiuM, Cardiff 1 May 2008. - Barlow, David M.; Johnson, Steve (Radio Journal: International Studies in Broadcast & Audio Media, 2008)
A report on a one-day research symposium on the role, sustainability, and practice of community radio that was held at the University of Glamorgan in Cardiff, Wales, on May 1, 2008. The symposium was organized in response to a rise in public and political interest in community radio in Wales that followed the launch of the so-called third tier of U.K. radio—after public service radio, the first tier, and commercial radio, the second—in 2002.